Use of Nd:YAG laser in bruise resolution caused by an injectable dermal filler procedure. Issue 3 (16th March 2022) - Dekeyser, Barry; Wellens, Marijke; Talaber, Iva
Abstract: Injectable dermal fillers are in high demand. Patients undergoing this treatment are frequently burdened by bruising in the days following the procedure. Bruises associated with dermal fillers usually resolve spontaneously within 10 to 14 days, but patients want shorter downtime. We present a case of a bruise treatment with Nd:YAG laser consisting of three sessions in two day intervals, where the bruise resolved after seven days from the start of laser treatment. To date, the reports on laser therapy for bruise resolution are mostly limited to intense pulsed light and pulsed dye laser, and this case report contributes to the demonstration of Nd:YAG laser efficacy for this indication. Abstract : Bruising or ecchymosis is a frequent adverse effect of injection and a primary concern to many patients considering injectable dermal fillers. Nd:YAG laser treatment can accelerate bruise resolution time and can therefore be used by medical practitioners to decrease downtime in patients undergoing this popular aesthetic procedure.